How Management Practices Within a Poultry House During Successive Flock Rotations Change the Structure of the Soil Microbiome - Crippen, Tawni L.; Sheffield, Cynthia L.; Singh, Baneshwar; Byrd, J. Allen; Beier, Ross C. (Frontiers in Microbiology, 2019)
The microbiome within a poultry production house influences the attainment of physiologically strong birds and thus food safety and public health. Yet little is known about the microbial communities within the house and the effects on the soil microbes onto which the houses are placed; nor the effects of management practices on their equilibrium. This study looked at the soil bacterial microbiome before a broiler house was constructed, then through 11 flock rotations (2.5 yrs) that included a partial clean-out and a total clean-out within the management regimen. Major shifts were observed, occurring at the taxonomic class level, related to the introduction of bedding and birds on top of the soil. The partial clean-out of litter did not change the soil bacterial community in any substantial way, only prompting a temporary increase in some genera; however, the total litter clean-out caused a major increase in a cohort of Actinobacteria. The underlying soil contained bacteria beneficial for poultry metabolism, such as Lactobacillus, Faecalibacterium, Bacteriodes and Ruminococcus. Therefore, the Native and Pad soil could be a source of some important intestinal bacteria and thus, should be considered as a management tool for seeding the poult digestive system with beneficial bacteria and to mitigate pathogenic species. Additionally, management practices affected the class structure of the soil bacterial community beneath the poultry house. The scheduling of these practices should be leveraged to exploit maintenance of beneficial bacteria that maximize microbiome contributions to bird production processes, while minimizing possible antibiotic-resistant bacteria and environmental effects.